Bioactivity effects of extracellular matrix proteins on apical papilla cells - Maria Luísa LEITE; Diana Gabriela SOARES; Giovana ANOVAZZI; MON Filipe Koon Wu; Ester Alves Ferreira BORDINI; Josimeri HEBLING; Carlos Alberto DE SOUZA COSTA (University of São Paulo, 2021)
Abstract Potent signaling agents stimulate and guide pulp tissue regeneration, especially in endodontic treatment of teeth with incomplete root formation. Objective This study evaluated the bioactive properties of low concentrations of extracellular matrix proteins on human apical papilla cells (hAPCs). Methodology Different concentrations (1, 5, and 10 µg/mL) of fibronectin (FN), laminin (LM), and type I collagen (COL) were applied to the bottom of non-treated wells of sterilized 96-well plates. Non-treated and pre-treated wells were used as negative (NC) and positive (PC) controls. After seeding the hAPCs (5×103 cells/well) on the different substrates, we assessed the following parameters: adhesion, proliferation, spreading, total collagen/type I collagen synthesis and gene expression (ITGA5, ITGAV, COL1A1, COL3A1) (ANOVA/Tukey; α=0.05). Results We observed greater attachment potential for cells on the FN substrate, with the effect depending on concentration. Concentrations of 5 and 10 µg/mL of FN yielded the highest cell proliferation, spreading and collagen synthesis values with 10 µg/mL concentration increasing the ITGA5, ITGAV, and COL1A1 expression compared with PC. LM (5 and 10 µg/mL) showed higher bioactivity values than NC, but those were lower than PC, and COL showed no bioactivity at all. Conclusion We conclude that FN at 10 µg/mL concentration exerted the most intense bioactive effects on hAPCs.